Pembelajaran Vokal Dengan Metode Demonstrasi pada Kelas X di SMAN 2 Toboali Kabupaten Bangka Selatan - Gunawan, Reza; Kurniawan, Irfan; Adoma, Auzy Madona (ANTHOR: Education and Learning Journal, 2022)
The purpose of this study was to determine how the vocal learning process using the demonstration method. In this study, the researcher used a qualitative descriptive approach. The object to be studied is the process of learning art and culture which is in terms of vocal learning with the demonstration method at SMA Negeri 2 Toboali. Teachers and students at SMA Negeri 2 Toboali who will be informants for this research. Data collection techniques are observation, interviews, documentation. Based on the results of the analysis of research data and the discussion contained in the previous chapter about vocal learning with the demonstration method in class X at SMA N 2 Toboali, South Bangka Regency. It can be concluded that vocal learning with the demonstration method in learning arts and culture is very helpful, especially vocal learning in class X SMA N 2 Toboali, because students more easily understand the material presented by the teacher so that learning takes place more efficiently. Based on the results of research data analysis and discussion contained in the previous chapter on vocal learning with the demonstration method in class X at SMA N 2 Toboali, South Bangka Regency. It can be concluded that vocal learning with the demonstration method in learning arts and culture is very helpful, especially vocal learning in class X SMA N 2 Toboali, because students understand the material presented by the teacher more easily so that learning takes place more efficiently.